Student internship success workbook 20+ lessons and activities for student intern career readiness (supervisor's guide) - Labor, Saby L. ([California] CreateSpace Independent Publishing Platform, 2017)
"The Student Internship Success Workbook is for college student." --from publisher's website.
"This book is part of the Student Internship Success Bundle. The student companion book is: Student Internship Success Workbook" -- Title page.
Resources available at: www.studentinternshipsuccess.com
Keywords: College students -- Vocational education; Internship programs; Occupational training; College graduates -- Employment